A community benchmark for viscoplastic thermal convection in a 2‐D square box. (14th July 2015) - Tosi, N.; Stein, C.; Noack, L.; Hüttig, C.; Maierová, P.; Samuel, H.; Davies, D. R.; Wilson, C. R.; Kramer, S. C.; Thieulot, C.; Glerum, A.; Fraters, M.; et al.
Abstract Numerical simulations of thermal convection in the Earth's mantle often employ a pseudoplastic rheology in order to mimic the plate‐like behavior of the lithosphere. Yet the benchmark tests available in the literature are largely based on simple linear rheologies in which the viscosity is either assumed to be constant or weakly dependent on temperature. Here we present a suite of simple tests based on nonlinear rheologies featuring temperature, pressure, and strain rate‐dependent viscosity. Eleven different codes based on the finite volume, finite element, or spectral methods have been used to run five benchmark cases leading to stagnant lid, mobile lid, and periodic convection in a 2‐D square box. For two of these cases, we also show resolution tests from all contributing codes. In addition, we present a bifurcation analysis, describing the transition from a mobile lid regime to a periodic regime, and from a periodic regime to a stagnant lid regime, as a function of the yield stress. At a resolution of around 100 cells or elements in both vertical and horizontal directions, all codes reproduce the required diagnostic quantities with a discrepancy of at most <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgj2frzj4k2" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />∼3%</alternatives> in the presence of both linear and nonlinear rheologies. Furthermore, they consistently predict the critical value of the yield stress at which the transition between different regimes occurs. As the most recent mantle convection codes can handle a number of different geometries within a single solution framework, this benchmark will also prove useful when validating viscoplastic thermal convection simulations in such geometries.